Private Property in Communist Czechoslovakia - Jan Demela; Štěpán Mikula (Review of Economic Perspectives, 2015)
This article analyses the development of legislation regarding private property in Czechoslovakia between 1948 and 1989 and summarizes available empirical data relating to property rights protection in the given period. Although the legislation took gradual steps towards diminishing the status of private property, no laws were passed that officially or entirely terminated its existence. The legislation of the 1960s set a status quo which codified property rights until the fall of the Communist regime in 1989. Most of the empirical data, which are available only for the 1980s, do not show any significant trend, corresponding with the unaltered situation in the legislation of that decade.
Keywords: 330